Modelling of manufacturing shop floor - Leung, Whye Keong. (2008)
Investigation of the feasibility and benefits of cellular manufacturing as compared to conventional layout in pharmaceutical industry, and also the possibility of reducing product contamination and improving the work flow of WIP goods.